Assessing Land Suitability for Lamtoro (Leucaena leucocephala) in Reclaimed Mining Lands of Sanggau Regency, West Kalimantan - Ichsannudin, Ichsannudin; Wahid, Muhammdan Abdul; Jalil, Abdul (Journal of Earth and Marine Technology (JEMT), 2024)
This study evaluates the suitability of reclaimed zircon mining land in Sanggau Regency, West Kalimantan for cultivating Lamtoro (Leucaena leucocephala), a versatile plant used for forage and as a biomass energy source. Utilizing the weight factor matching method, we analyzed a range of land characteristics including soil texture, drainage, pH, and organic carbon content, as well as environmental factors such as temperature and rainfall. Initial assessments categorized the land as marginally suitable due to suboptimal drainage and soil texture. However, our research suggests that through strategic interventions—specifically improving soil texture using topsoil and enhancing drainage systems—the suitability of the land can be significantly upgraded. Detailed analysis shows that with these modifications, the land shifts from a marginal to a highly suitable rating for Lamtoro cultivation. The successful adaptation of Lamtoro in these reclaimed areas not only supports agricultural viability but also aids in the ecological restoration of post-mining landscapes, contributing to the achievement of sustainable development goals. This study underscores the potential of targeted land management strategies in transforming degraded mining areas into productive agricultural lands, providing a blueprint for similar reclamation efforts globally.